Crear y reflexionar para aprender : diseño de una secuencia didáctica para potenciar los procesos de escritura a través de la creación artística en estudiantes de primaria (2020)
Art and writing are two languages that allow the expression and communication of ideas, feelings, emotions and perceptions. The integration of these two languages can have positive impacts on the process of artistic and scriptural creation through constant reflection. This work seeks to identify how the integration between writing and art can enhance the writing processes of 5th grade students. The proposal is based on a diagnosis, at the San Bartolomé La Merced School, in which some institutional documents, interviews with language and plastic arts teachers, and a pedagogical approach to some students were analyzed. Subsequently, a process of designing a didactic sequence that responds to the subject of study began. As theoretical underpinnings for the proposal, we start from a teaching and learning posture based on sociocultural constructivism, the Teaching for Understanding (EpC) framework and some approaches to the teaching of writing and art. The results indicate that, from the development of a didactic sequence in which the integration of writing and art is taken into account, communicative values, children's interest in artistic creation and reflection can be strengthened immersed in this, and the writing processes.